Northwest History. Alaska. Dogs, Dog Races & Mushers. (1936)
'Plenty Scared,' White Woman Admits Makes 1000-Mile Trip With Dog Sled Crosses Rivers On Floating Ice Cakes. 'Plenty Scared', WhiteWoman Admits Makes 1000-Mile Trip With Dog Sled Crosses Rivers On Floating Ice Cakes SKAGWAY, Alaska, Jan. 28. (JP)—Mary Joyce, diminutive but venturesome proprietress of a Taku river hunting lodge, travelled alone but for her sled dogs today on the snowy trail between Whitehorse and Kluane, Y. T., second major leg in her 1,000-mile journey from Juneau to Fairbanks. She left Whitehorse Sunday after resting from a speedy 225-mile trip through deep snows and treacherous ice from her home at Twin Glaciers via Tulsequah and Atlin, B. C. She is carrying cameras, lots of film and a letter from Territorial Gov. John W. Trov to Fairbanks' mayor. E. C. Collins. Her journal of the first part of the trip, published by the Juneau Empire, told how she left home on the hazardous trip Dec. 20 "just for the experience," and of her trail impressions. "For the first time in my life," she write, "I have seen blue water -- the color of icebergs -- water fast, cold and cruel running between icy banks. Travelled on gravel bars, crossing the channels (headwaters of the glacier fed Taku river) on log sweepers, with poles from the logs to the ice on the oppostie shores. "Plenty Scared" "Chocack Lacgoose -- Billy Williams to you (her guide at the start of the trip) -- scolded his sons and made them put boughs over the holes so I could not see the water underneath. "White lady plenty scared!" Crossed on my hands and knees and my dogs followed like soldiers. "Put a chain on Tip (her lead dog) and each dog fell in the water. Pulled them out onto another cake of ice. Ice two feet wide, in places just room for the sled with water gurgling underneath and leaping over. I made it -- but they had a chain on me, too. "Followed the Naxima river. Ice two feed wide, in places just room for the sled with water gurgling underneath and leaping over. I made it -- but they had a chain on me, too. "Followed the Naxima river. Ice on the bank and open water on one side. My movie camera bounded into the water. Fished it out with gaff hook made of poles. From Canoe Navigation two Indians went back. I started up Sloko mountain with Lakutata Sladanta -- otherwise Frank Williams --with his sled and two dogs carrying smoked salmon and my sleeping bag. Called a "Nobody" "Hit the trail to Hot Springs. Travelled 20 miles thorugh deep, fluffy snow. Frank breaking trail. Hurt my shoulder lifting handle bars. Finally came to a farm. The light in the window looked so good. Rapped on the door and asked to be let in to get warm. A voice told me. "Go away, you nobody." After I got out of rifle range I learned the old mand had extended hospitality to others and got two black eyes for his pains. "We mushed on, dogs" tongues out and crawling on their bellies through the deep snow. I felt so sorry for them until we came to fresh moose tracks. They cocked their ears, curled their tails and all I could do was keep on the trail.